Letter from Max Bredig to Marianne and Viktor Homburger, January 4, 1940 - Bredig, Max Albert (1940)
Max Bredig (1902-1977) tells Marianne Homburger (1903-1987) and Viktor Homburger (1888-1968), who are currently interned in the Gurs concentration camp, that he has sent them packages. He also mentions that their children are doing well in England.
Keywords: Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986; Gurs (Concentration camp)